(untitled) (Ethiopian Journal of Economics, 2011)
This paper has examined the spatial integration, price dynamics, and pricingbehavior of wheat markets in Ethiopia using 72 months retail price series (July2001‐June 2007) and cross‐section data of structural determinants of spatialintegration. Dynamic measures of spatial integration including long‐runmultipliers, speed of spatial price adjustment, and composite index wereestimated to measure the magnitude, speed, and extent of spatial linkages andto identify the relative importance and pricing conduct in these markets. Thecommon assertion that Addis Ababa is a central market dictating commodityprice formation process in Ethiopia was disproved. Nazreth wheat market wasfound to be the center of price discovery in the country by dictating priceformation in supply markets. The three hypothesized oligopolistic pricingbehavior of wheat markets— spatial price discrimination, instantaneous andcooperative pricing, and perfect price matching — were tested. The twohypotheses that wheat markets exercise spatial price discrimination andcooperative pricing were rejected. However, the hypothesis of spatial pricediscrimination was accepted for some markets trading with Addis Ababa andNazreth. This is verified to be the result of price discrimination exercised in AddisAbaba and the response of supply markets against the conduct in the destination markets. Supply markets with alternative market outlets were tryingto establish short‐run market independence depending on the pricing conductprevalent in the destination markets while those without alternative marketoutlets were victims of the pricing behavior. This is an indication of inefficientpricing system prevalent in the wheat marketing system. Structuraldeterminants of spatial market integration including inter‐market road distance,road density, dissimilarity in per capita wheat production, and dissimilarity inpopulation density were estimated and tested for their possible effect on thelevel, speed and extent of market integration to identify alternative marketdevelopment interventions. Except for population density, all the selectedfactors of market integration were found to significantly determine marketintegration in Ethiopia. The spatial integration of Ethiopian wheat markets wasfound to be generally low in magnitude and sluggish in speed because of lack offlexibility and responsiveness of the marketing system.